Structural and Biochemical Analysis of OrfG: The VirB8-like Component of the Conjugative Type IV Secretion System of ICESt3 From Streptococcus thermophilus - Cappele, Julien; Mohamad Ali, Abbas; Leblond-Bourget, Nathalie; Mathiot, Sandrine; Dhalleine, Tiphaine; Payot, Sophie; Savko, Martin; Didierjean, Claude; Favier, Frédérique; Douzi, Badreddine (Frontiers in Molecular Biosciences, 2021)
Conjugative transfer is a major threat to global health since it contributes to the spread of antibiotic resistance genes and virulence factors among commensal and pathogenic bacteria. To allow their transfer, mobile genetic elements including Integrative and Conjugative Elements (ICEs) use a specialized conjugative apparatus related to Type IV secretion systems (Conj-T4SS). Therefore, Conj-T4SSs are excellent targets for strategies that aim to limit the spread of antibiotic resistance. In this study, we combined structural, biochemical and biophysical approaches to study OrfG, a protein that belongs to Conj-T4SS of ICESt3 from Streptococcus thermophilus. Structural analysis of OrfG by X-ray crystallography revealed that OrfG central domain is similar to VirB8-like proteins but displays a different quaternary structure in the crystal. To understand, at a structural level, the common and the diverse features between VirB8-like proteins from both Gram-negative and -positive bacteria, we used an in silico structural alignment method that allowed us to identify different structural classes of VirB8-like proteins. Biochemical and biophysical characterizations of purified OrfG soluble domain and its central and C-terminal subdomains indicated that they are mainly monomeric in solution but able to form an unprecedented 6-mer oligomers. Our study provides new insights into the structural analysis of VirB8-like proteins and discusses the interplay between tertiary and quaternary structures of these proteins as an essential component of the conjugative transfer.